Experimental investigation of effects of coolant concentration on subcooled boiling and crud deposition on reactor cladding at high pressures and high temperatures - Paravastu Pattarabhiran, Vijaya Raghava (Kansas State University, 2008)
Increase in demand for energy necessitates nuclear power units to increase their peak power limits. This increase implies significant changes in the design of the nuclear power unit core in order to provide better economy and safety in operations. A major hindrance to the increase of nuclear reactor performance especially in Pressurized Water Reactors (PWR) is the so called ‘Axial Offset Anomaly (AOA)’. An Axial Offset Anomaly (AOA) is the unexpected change in the core axial power distribution during the operation of a PWR from the predicted distribution. This problem is thought to be occurring because of precipitation and deposition of lithiated compounds such as lithium metaborate (LiBO[subscript]2) on the fuel rod. Due to its intrinsic property, the deposited boron absorbs neutrons thereby affecting the total power distribution in the reactor. AOA is thought to occur when there is sufficient build up of crud deposits on the cladding during subcooled nucleate boiling. Predicting AOA is difficult because there is little information regarding the heat and mass transfer during subcooled nucleate boiling. This thesis describes the experimental investigation that was conducted to study the heat transfer characteristics during subcooled nucleate boiling at prototypical PWR conditions. Pool boiling tests were conducted with varying concentrations of LiBO[subscript]2 and boric acid (H[subscript]2BO[subscript]3) solutions along with deionized water. The experimental data collected includes the effect of coolant concentration, degree of subcooling, system pressure and heat flux on pool boiling heat transfer coefficients. An analysis of deposits formed on the fuel rod during subcooled nucleate boiling is also included in the thesis. The experimental results reveal that the pool boiling heat transfer coefficient is degraded by the presence of boric acid and lithium metaborate in water. At concentration of 5000 ppm in water, the boric acid solution reduced the heat transfer coefficient by 23% and lithium metaborate solution reduced the heat transfer coefficient by 26%.
Keywords: Pool Boiling Heat Transfer; Crud deposition; Subcooled Boiling; Axial Offset Anomaly; Coolant Concentration; Engineering, Mechanical (0548); Engineering, Nuclear (0552)